Toxic epidermal necrolysis caused by viral hepatitis A: a case report and literature review - Ye, Yun; Zhang, Qian; Tan, You-Wen (Frontiers in Medicine, 2024)
Toxic epidermal necrolysis (TEN) is a rare but serious immune-mediated life-threatening skin and mucous membrane reaction that is mainly caused by drugs, infections, vaccines, and malignant tumors. A 74-year-old woman presented with a moderate fever of unknown cause, which was relieved after two days, but with weakness and decreased appetite. Red maculopapules appeared successively on the neck, trunk, and limbs, expanding gradually, forming herpes and fusion, containing a yellow turbidous liquid and rupturing to reveal a bright red erosive surface spreading around the eyes and mouth. The affected body surface area was >90%. The severity of illness score for toxic epidermal necrolysis was 2 points. The drug eruption area and severity index score was 77. She was diagnosed with TEN caused by hepatitis A virus and treated with 160 mg/day methylprednisolone, 300 mg/day cyclosporine, and 20 g/day gammaglobulin. Her skin showed improvements after 3 days of treatment and returned to nearly normal after 1 month, and liver function was completely normal after 2 months.